War as a business and the civil war businesses in 1851 (2013)
Hispano-American civil wars traditionally have been an important factor of political instability and economic insecurity. They had been pointed out as an important cause of national backwardness and underdevelopment in the nineteenth century. However,these representations have been built with many prejudices and little study, by foreigners and international observers. New research has succeeded in clarifying the political and economic significance of the wars , and in this sense , this article provides an overview of the Civil War of 1851 from its economic and social costs,the financial and management problems involving the State of New Granada,its harmful effects on public spending and how it disrupted the rhythms of work and domestic production. Even so , this conflict,like every plight assumed by the nineteenth-century state ,also led to its agencies and bureaucrats to work efficiently and rationality, with sensitivity to public matters,and serve as a body for the management and control over the population and the territory. In any case , despite its feared effects , the war was not a total disaster for the economy. It stimulated a questionable scenario for traders,speculators and contractors who sought access to public resources in a rather restricted economic context.